2017
DOI: 10.1002/ps.4491
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of 3‐hydroxy‐2‐hexanone and ethanol as attractants for the cerambycid beetle pest of vineyards, Xylotrechus arvicola

Abstract: BACKGROUND: The beetle Xylotrechus arvicola (Coleoptera: Cerambycidae) is a serious pest of vineyards in the Iberian Peninsula. In previous work, the male beetles, but not females, were shown to produce (R)-3-hydroxy-2-hexanone, and female beetles were attracted to this compound in a laboratory bioassay. In this study, release rates of 3-hydroxy-2-hexanone from different dispensers were measured in the laboratory, and the attractiveness of these to X. arvicola adults was determined in trapping tests in three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Interception traps (Crosstrap, Econex, Murcia, Spain), baited with ethanol as recommended by Rodríguez-González et al (2017c), were used to capture X. arvicola adults. Captured adults were paired (one female and one male) and introduced into glass jars (80 mm in diameter and 100 mm high).…”
Section: Methodsmentioning
confidence: 99%
“…Interception traps (Crosstrap, Econex, Murcia, Spain), baited with ethanol as recommended by Rodríguez-González et al (2017c), were used to capture X. arvicola adults. Captured adults were paired (one female and one male) and introduced into glass jars (80 mm in diameter and 100 mm high).…”
Section: Methodsmentioning
confidence: 99%
“…The Crosstrap was selected as the reference trap because this type of trap had been widely used for the control of other cerambycids [ Monochamus galloprovincialis (Olivier)], described as a plague in woody crops ( Pinus spp.) from several countries (Álvarez et al ), and because, it was the trap type that had been used in the previous tests for the evaluation in the field of the compounds 3‐hydroxy‐2‐hexanone and ethanol as attractants of X. arvicola adults (Rodríguez‐González et al ). The Delta trap was chosen because it has also been used to capture and control other insects whose larvae are wood borers, Synanthedon scitula Harris (Lepidoptera: Sesiidae) (Zhang et al ), or insect pests that also affect the vineyard and whose larvae are fruit borers, Lobesia botrana Denis & Schiffermüller (Lepidoptera: Tortricidae) (Rayegan et al ) or Paralobesia viteana Clemens (Lepidoptera: Tortricidae) (Dong et al ).…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, Hall et al () observed that X. arvicola male beetles produced the compound 3‐hydroxy‐2‐hexanone in a wind tunnel test, where females showed attraction for males's compound (3‐hydroxy‐2‐hexanone), but this attraction was not observed in preliminary trapping trials in the field in Spain. Rodríguez‐González et al () carried out further field testing on the compound 3‐hydroxy‐2‐hexanone and on different designs of lures in several Spanish vineyards. Although in previous studies females showed attraction to 3‐hydroxy‐2‐hexanone in wind tunnel tests, no attractive effects were demonstrated in field experiments again.…”
Section: Introductionmentioning
confidence: 99%
“…A pheromone is produced by males to attract females (Hall et al, 2007;Rodríguez-González et al, 2017) but it is not effective in traps (Armendáriz et al, 2016). There is no indication of how adults localize vines, although the use of visual clues, aggregation pheromones or specific kairomones might be involved, either alone or in combination.…”
Section: Introductionmentioning
confidence: 99%